Analysis of In-wheel asynchronous motor with conical geometry for electric vehicle - AKÜNER, MUSTAFA CANER; DEMİR, UĞUR (My University, 2018)
The purpose of this study is to optimize the package geometry in wheel motors for an electric vehicle. In this context, it is aimed to analyze and design in-wheel asynchronous motor with a conical geometry for an electric vehicle. Thus, an asynchronous motor with a conical geometry and in-wheel asynchronous motor with a radial flux have been evaluated by comparing performance against each other within the package boundaries. An asynchronous motor design for the required performance requirements was realized by using the Ansys RMXprt program. The package analysis for the designed asynchronous motor was performed and the minimum and maximum package sizes for in-wheel asynchronous motor. The motor with conical geometry which is designed as a tapered geometry in 3D according to the minimum and maximum dimensions. In the Ansys Maxwell program, these 3 type motors were analyzed in terms of the rated torque, the rated revolution, the starting torque, the breakdown torque, the power factor, the efficiency and the magnetic flux on the rotor and the stator. It has been seen that every motor has advantages and disadvantages in the study. In this context, an asynchronous motor with a conical geometry may provide optimization for the desired properties.
Keywords: Conical Motor; Finite Element Method; Electrical machines; Asynchronous motor; In-wheel motor